Conjunctival intraepithelial neoplasia and carcinoma: distinct clinical and histological features in relation to human papilloma virus status. Issue 6 (24th October 2019) - Ramberg, Ingvild; Toft, Peter Bjerre; Georgsen, Jeanette Bæhr; Siersma, Volkert Dirk; Funding, Mikkel; Jensen, David Hebbelstrup; von Buchwald, Christian; Heegaard, Steffen
Abstract : Aims: Human papillomavirus (HPV) is considered a causative agent for the development of a broad range of human carcinomas. The role of HPV in the development of conjunctival intraepithelial neoplasia (CIN) and carcinoma (cSCC) remains unclear. The purpose of the present study was to investigate the HPV prevalence in a nationwide cohort and to describe clinical and histopathological features in relation to HPV status. Methods: All cases of CIN and cSCC in Denmark from 1980 to 2016 were included. We combined p16 immunohistochemistry (IHC), RNA in situ hybridisation (RNA ISH) and HPV DNA PCR to detect HPV. The results were correlated to clinical and histopathological parameters. Results: One hundred twelve primary tumours and 33 recurrent tumours were included for HPV analysis. Twenty-four (21%) of the primary tumours were HPV positive by PCR. Eighteen of out 19 HPV-positive tumours were positive by RNA ISH. HPV16 was the most prevalent genotype (n=18, 75%). The patients with HPV-positive tumours were significantly younger (mean difference 11.5 years, 95% CI 5.2 to 17.9, p=0.0005) and had a higher recurrence compared with patients with HPV-negative tumours (HR 2.30, 95% CI 1.02 to 5.21, p=0.046). The HPV-positive tumours were associated with a positive p16 IHC and a non-keratinising morphology. Conclusion: We describe distinct clinical and histopathological features associated with HPV status in cSCC. The finding of transcriptionally active HPV in this material lends support to a causal role of HPV in a subset of cSCC.